Logística de suprimentos: um estudo de caso sobre controle de abastecimento de mercadorias da empresa V. S. Garcia - Garcia, Anderson Abreu (BRASIL, 2022)
Logistics plays an important role in the general context of a company, because with the growth of competitiveness in the market, organizational functions are very important in the business field. The supply chain is one of the most important elements in a company's activity, as it is the life that keep the company running active and strong in the market. The present case study was developed through observations and interviews with the company V.S. Garcia (Mercadinho do Barriga), a company located in the Municipality of Benjamin Constant- Amazonas, with the objective of understanding how the structure of the company's supply chain works, presenting certain points in the process as well as in the ordering of goods, transport and storage. Entering the great challenges of the logistics process in the Amazon region, such as climatic factors that are faced every year: times of drought and flooding of the rivers. As the company is located in the interior region of the Amazon (Alto Solimões), the logistics process has greater factors, compared to the other logistics process outside, because the company, to keep its supply chain up to date, needs outsourced services . The major challenges to maintain the supply chain have as direct aspects in the company's activity, as problems such as weather factors and outsourced logistics processes that are beyond the control of the company and end up causing great inconvenience to the company. More in the face of these factors, the company continues to remain firm and strong in the market and having its clientele.